Carbon Stocks in Silvopastoral Systems: A Study from Four Communities in Southeastern Ecuador. (8th June 2015) - McGroddy, Megan E.; Lerner, Amy M.; Burbano, Diana V.; Schneider, Laura C.; Rudel, Tom K.
Abstract Agriculture, particularly pasture, is the second largest source of greenhouse gas emissions from tropical regions. Silvopastoral systems may increase carbon pools in pastures while maintaining productivity. Adding trees to pasture provides carbon sinks in woody biomass, and may improve degraded soils and increase the stability of soil carbon pools. In this study we quantified the biomass carbon stored in spontaneous silvopastoral systems in southeastern Ecuador. We compared the stem density, basal area, aboveground biomass, and organic carbon in the top 20 cm of soil in 100 pastures, ranging from 3 to 250 hectares, in four different communities. Aboveground live woody biomass, calculated using allometric equations and two different wood densities, varied from 10.99 to 66.1 Mg per hectare. Soil organic carbon pools ranged from 85.0 to 97.6 Mg per hectare. Stem density, basal area, and aboveground live biomass all positively correlated with pasture age. We found no relationship between pasture age or stem density and soil organic carbon pools. We measured live woody biomass carbon pools of 34–1070 Mg of carbon per farm in these silvopastoral systems. We found no effects on productivity of the herbaceous layer, suggesting that having a low density of trees in pastures could substantially increase the number of trees and the associated carbon sequestration without affecting cattle production.